SINKRONISASI GENERATOR 635 KVA DENGAN GENERATOR 635 KVA MENGGUNAKAN MODULE DEEP SEA - Nurul Fahmi Sahputra; Eddy warman; Agus Almi Nasution (Jurnal Simetri Rekayasa, 2021)
In the operation of a generator, it must be carried out in a short time to adjust the voltage and frequency required at the load and also equalize between generator 1 and the others. If the synchronization operation of the generator is done manually by the operator, it takes time and a level of accuracy. Therefore, research related to the synchronization of generators with generators using the Deep Sea Electronic Module 8610 was carried out. By doing this research, it is hoped that later it can help the generator operation process so that generator 1 and generator 2 can work by sharing the load when used. The Deep Sea Elektonic 8610 module is a tool that is used to synchronize between generators and generators and can start and stop generators properly automatically and is able to protect in case of disturbances, both under voltage, over voltage, over load, reverse power relay, and failure phases. voltage. This system works automatically when the PLN electricity supply is cut off, if this situation occurs, the generator start-stop system will automatically activate and for 15 seconds the load can be supplied by the generator. When PLN electricity has arrived, the deep sea module will transfer the load to PLN and synchronize the two generators, enter colling down, then turn off the generator, and the generator will be in standby again.